Exposing medical students to Pecha Kucha during their training period: Need of the hour - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2021)
A medical doctor in the current generation is bound to get exposed to a wide range of scenarios, wherein they are expected to share their thoughts, ideas, expertise in a convincing and appealing way to the public. In order to improve the attention of the audience, we have to resort to something which is innovative, creative, yet concise and appealing. Pecha Kucha is a method of presentation which is designed to maintain interest of the audience, especially during the course of a series of presentations. However, we have to accept that only adoption of the Pecha Kucha format won't do wonders unless it is supplemented with good communication skills, positive body language and modulation of tone. In conclusion, the format of Pecha Kucha is a learner-centered approach with an aim to improve the attention span of the audience and ensure that the presentation is not being extended beyond time limits. In-fact, it has to be considered as an approach to improve the speaker abilities with regard to abstraction, analysis, and synthesis.